Currency and the Stability of People's Purchasing Power in Indonesia through Al-Maqrizi's Review - Mirza Purta Ashari (Universitas Nahdlatul Ulama Surabaya, 2021)
The presence of money has become an important part of people's daily lives, as well as the purchasing power of the people as an important element in the smooth economic cycle. The emergence of money came from the development of transactions that initially used barter which was later replaced by currency as a medium of exchange for international trade. Money management can be done by the government by controlling money in the form of monetary policy. This policy was a benchmark for a country's economy, when the state was able to control money well, the people's economy was also prosperous. The qualitative descriptive approach was used in this study. This article tried to provide views and discussion material to what extent the concept of monetary policy according to Al-Maqrizi and the implementation of his thinking was used in policymaking on people's purchasing power. The result of this research was that the concept offered by Al-Maqrizi was a concept of money that led to a moral, just, humane, and prosperous economy.The presence of money has become an important part of people's daily lives, as well as the purchasing power of the people as an important element in the smooth economic cycle. The emergence of money came from the development of transactions that initially used barter which was later replaced by currency as a medium of exchange for international trade. Money management can be done by the government by controlling money in the form of monetary policy. This policy was a benchmark for a country's economy, when the state was able to control money well, the people's economy was also prosperous. The qualitative descriptive approach was used in this study. This article tried to provide views and discussion material to what extent the concept of monetary policy according to Al-Maqrizi and the implementation of his thinking was used in policymaking on people's purchasing power. The result of this research was that the concept offered by Al-Maqrizi was a concept of money that led to a moral, just, humane, and prosperous economy.